Mechanisms of NFATc3 activation by increased superoxide and reduced hydrogen peroxide in pulmonary arterial smooth muscle - Ramiro-Diaz, Juan Manuel (Am J Physiol Cell Physiol, 2014)
We recently demonstrated increased superoxide (O(2)(·−)) and decreased H(2)O(2) levels in pulmonary arteries of chronic hypoxia-exposed wild-type and normoxic superoxide dismutase 1 (SOD1) knockout mice. We also showed that this reciprocal change in O(2)(·−) and H(2)O(2) is associated with elevated activity of nuclear factor of activated T cells isoform c3 (NFATc3) in pulmonary arterial smooth muscle cells (PASMC). This suggests that an imbalance in reactive oxygen species levels is required for NFATc3 activation. However, how such imbalance activates NFATc3 is unknown. This study evaluated the importance of O(2)(·−) and H(2)O(2) in the regulation of NFATc3 activity. We tested the hypothesis that an increase in O(2)(·−) enhances actin cytoskeleton dynamics and a decrease in H(2)O(2) enhances intracellular Ca(2+) concentration, contributing to NFATc3 nuclear import and activation in PASMC. We demonstrate that, in PASMC, endothelin-1 increases O(2)(·−) while decreasing H(2)O(2) production through the decrease in SOD1 activity without affecting SOD protein levels. We further demonstrate that O(2)(·−) promotes, while H(2)O(2) inhibits, NFATc3 activation in PASMC. Additionally, increased O(2)(·−)-to-H(2)O(2) ratio activates NFATc3, even in the absence of a G(q) protein-coupled receptor agonist. Furthermore, O(2)(·−)-dependent actin polymerization and low intracellular H(2)O(2) concentration-dependent increases in intracellular Ca(2+) concentration contribute to NFATc3 activation. Together, these studies define important and novel regulatory mechanisms of NFATc3 activation in PASMC by reactive oxygen species.